Histoires d’identité (génétique) - Anne-Louise Leutenegger; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This note takes a historical perspective on the concept of genetic identity states between four alleles of two individuals. Several definitions of these states were proposed between 1940 and 1970, and states were diversely merged according to the authors. The historical analysis of the publications shows that the definition and the description of the identity states occurred quasi-simultaneously and most probably independently both in France and in the United States of America.